Amphiphilic Dendrimer Doping Enhanced pH‐Sensitivity of Liposomal Vesicle for Effective Co‐delivery toward Synergistic Ferroptosis–Apoptosis Therapy of Hepatocellular Carcinoma. Issue 6 (30th January 2023) - Su, Yanhong; Zhang, Zhao; Lee, Leo Tsz On; Peng, Ling; Lu, Ligong; He, Xu; Zhang, Xuanjun
Abstract: Ferroptosis, characterized by the accumulation of reactive oxygen species and lipid peroxides, has emerged as an attractive strategy to reverse drug resistance. Of particular interest is the ferroptosis–apoptosis combination therapy for cancer treatment. Herein, a nanoplatform is reported for effective co‐delivery of the anticancer drug sorafenib (S) and the ferroptosis inducer hemin (H), toward synergistic ferroptosis–apoptosis therapy of advanced hepatocellular carcinoma (HCC) as a proof‐of‐concept study. Liposome is an excellent delivery system; however, it is not sufficiently responsive to the acidic tumor microenvironment (TME) for tumor‐targeted drug delivery. The pH‐sensitive vesicles are therefore developed (SH‐AD‐L) by incorporating amphiphilic dendrimers (AD) into liposomes for controlled and pH‐stimulated release of sorafenib and hemin in the acidic TME, thanks to the protonation of numerous amine functionalities in AD. Importantly, SH‐AD‐L not only blocked glutathione synthesis to disrupt the antioxidant system, but also increased intracellular Fe 2+ and ·OH concentrations to amplify oxidative stress, both of which contribute to enhanced ferroptosis. Remarkably, high levels of ·OH also augmented sorafenib‐mediated apoptosis in tumor cells. This study demonstrates the efficacy of ferroptosis–apoptosis combination therapy, as well as the promise of the AD‐doped TME‐responsive vesicles for drug delivery in combination therapy to treat advanced HCC. Abstract : This research reports a pH‐sensitive hybrid liposomal vesicle (SH‐AD‐L) based on amphiphilic dendrimer, 1, 2‐dipalmitoyl‐sn‐glycero‐3‐phosphocholine, 1, 2‐distearoyl‐sn‐glycero‐3‐phosphoethanolamine‐N‐[methoxy (polyethylene glycol)‐2000], and cholesterol, with sorafenib and hemin co‐encapsulation. Hemin synergizes with sorafenib to disturb redox homeostasis and amplify oxidative stress via triggering GSH depletion, iron overloading, and ·OH production, which further induce efficient tumor suppression via synergistic ferroptosis–apoptosis for advanced hepatocellular carcinoma therapy.